(3cJGH GdbSe GdEdgi HGdGSe GdQHGfjs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO aEf Gddg Ld GSeg CbSe ai cJGHg GdYRjR Ydi CehQ cKjQI ai ehGVY TJi HCfhGY ef GdeNdhbGJ ef GdMQha hGdQjGM s
(3BNQgG (B:s
(3eZQH GdCQhGM CfaGS GdQjGM eTQb GdCSQGQ TQhb GdESJXgGQ eZQH GdCSQGQ eTGgOI GdXgGQ dGjSHb dEQJHGW GdehLhOGJ HGdMb Je GdcJGH hGdMeO ddg Mb MeOg s
(3HgG fXGe GdJYbjHIs
(3cJHgG GdfGSN Yf fSNI GdeUfa GdJi HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
Keywords: (3GdJUha hGdBOGH GdTQYjIs